2011
DOI: 10.1097/mnm.0b013e3283457466
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular fluid volume and glomerular filtration rate

Abstract: In unselected patient populations, there is no correlation between GFR and ECV. The CV of ECV is slightly higher in patients than healthy individuals but, in both, is less than the CV of GFR. These data do not detract from the use of slope-only GFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…An increase in ECFV can occur in end stage renal disease in human patients and ECFV increases in the early stages of CKD by approximately 8% 23. Human patients show a progressive increase in ECFV with declining GFR,23, 24 although there is no correlation between GFR and ECFV in human patients across a range of GFR 25. In this study, there was no significant difference in ECFV between nonazotemic and azotemic cats.…”
Section: Discussioncontrasting
confidence: 52%
“…An increase in ECFV can occur in end stage renal disease in human patients and ECFV increases in the early stages of CKD by approximately 8% 23. Human patients show a progressive increase in ECFV with declining GFR,23, 24 although there is no correlation between GFR and ECFV in human patients across a range of GFR 25. In this study, there was no significant difference in ECFV between nonazotemic and azotemic cats.…”
Section: Discussioncontrasting
confidence: 52%
“…GFR can be determined by measuring renal clearance of an intrinsic or extrinsic agent that is freely filtered by the glomeruli (6,7). Inulin clearance has been widely believed to be the gold standard for GFR studies, but it is relatively invasive and not easy to perform in everyday practice (8). Measurement of Tc-99m diethylenetriamine pentaacetic acid (Tc-99m DTPA) plasma clearance is used by many institutions for the determination of total GFR due to its simplicity and precision (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier inulin clearance used to be considered the gold standard for GFR studies, but it is relatively invasive and not easy to perform in routine clinical practice. [5] Currently, estimation of Tc-99m diethylenetriaminepentaacetic acid ( 99m Tc-DTPA) plasma clearance is used for the determination of global GFR due to its simplicity and precision. [6789] It is also reported that there is a correlation between 99m Tc-DTPA and inulin clearances when measuring GFR in clinical applications.…”
Section: Introductionmentioning
confidence: 99%